Different dose series of human papillomavirus vaccine in young females: a pair-wise meta-analysis and network meta-analysis from randomized controlled trials - Kemin, Li; Mengpei, Zhang; Jing, Zeng; Rutie, Yin (Frontiers in Public Health, 2023)
Objective: To investigate the application value of different dose of HPV vaccine in young females. Data sources: the following databases were searched: Cochrane Library, PubMed, Embase, Web of Science, SINOMED and Wanfang Data, from the establishment of the database to August 1 st , 2022. Study eligibility criteria: The inclusion criterias were: healthy young women younger than 25 years old as the research object, randomized controlled study as the research type, and the efficacy and safety of single-dose, two-dose or three-dose HPV vaccines as the intervention measures and research endpoints. Study appraisal and synthesis methods: Meta-analysis was performed to analyze the protective effects of single-dose, 2-dose and 3-dose HPV vaccine series on young females. Results: A total of eight eligible studies involving 16 publications were included. There is no difference in the immunogenicity between the 2-dose and 3-dose series within 12 months after the last dose of HPV vaccine. However, 3-dose series was better than the 2-dose series, which performed better than the single-dose vaccine, after 12 months. With respect to the prevention of HPV16/18 infection or HPV31/33/45 infection, the single-dose vaccine worked better than 2-dose or 3-dose series. Conclusions: The present study showed that the immunogenicity of low-dose HPV vaccine was significantly less, but it reduced the risk of high-risk HPV infection. The low-dose HPV vaccine series may not offer a preventive effect on cervical lesions, though it needs to be further confirmed by additional studies.